2017
DOI: 10.3906/sag-1609-26
|View full text |Cite
|
Sign up to set email alerts
|

Impact of GGCX polymorphisms on warfarin doserequirements in atrial fibrillation patients

Abstract: Background/aim: Warfarin is a common anticoagulant with large interindividual differences and a narrow therapeutic range. The polymorphisms of gamma-glutamyl carboxylase (GGCX) are important genetic factors for warfarin dose requirements. Materials and methods:Polymerase chain reaction and direct sequencing methods were used to detect the GGCX rs699664 genotype in 215 atrial fibrillation (AF) patients with warfarin administration. The effects on warfarin dose by different genotypes were analyzed. A warfarin do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Therefore, we strongly suggest that it is inappropriate to sequence VKORC1 for multiple loci to avoid unnecessary resource wastage. Furthermore, our study found that the effect of GGCX rs699664 on the daily stable dose of warfarin was statistically significant, which is consistent with the findings of Jiang et al [ 19 ] We first retained this SNP in the final model after stepwise screening, which accounted for 2% of the individual differences. GGCX rs699664 may be an important predictor in the warfarin dose algorithm, but further research is needed in the future.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, we strongly suggest that it is inappropriate to sequence VKORC1 for multiple loci to avoid unnecessary resource wastage. Furthermore, our study found that the effect of GGCX rs699664 on the daily stable dose of warfarin was statistically significant, which is consistent with the findings of Jiang et al [ 19 ] We first retained this SNP in the final model after stepwise screening, which accounted for 2% of the individual differences. GGCX rs699664 may be an important predictor in the warfarin dose algorithm, but further research is needed in the future.…”
Section: Discussionsupporting
confidence: 91%
“…For CYP1A2 rs2069514, our results were inconsistent with those of Liu et al, [ 16 ] which may be due to the fact that their study subjects were from the Northern Chinese population. Regarding UGT1A1 rs887829, Thai scholars reported results that were consistent with ours and also confirmed its lack of contribution to the model, [ 19 ] which was contrary to the findings of Korean scholars whose research also focused on Asians [ 20 ] and the specific reasons remain to be discussed.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…. In this study, CT and TT genotypes of GGCX rs2592551 gene polymorphism were found to be associated with higher warfarin dose requirements than CC genotype in patients with AF [14,15]. It is presented primer sequences that used to determine GGCX rs699664, rs2592551 gene polymorphisms in Table 6.…”
Section: Genes Primer Primer Sequencesmentioning
confidence: 94%